2014
DOI: 10.1093/jrr/rru074
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endogenous control gene(s) for gene expression studies in human blood exposed to 60 Co γ-rays ex vivo

Abstract: In gene expression studies, it is critical to normalize data using a stably expressed endogenous control gene in order to obtain accurate and reliable results. However, we currently do not have a universally applied endogenous control gene for normalization of data for gene expression studies, particularly those involving 60Co γ-ray-exposed human blood samples. In this study, a comparative assessment of the gene expression of six widely used housekeeping endogenous control genes, namely 18S, ACTB, B2M, GAPDH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The employment of this method allowed us to calculate that 1 ng of the “pooled sample” contained approximatively 5822 copies of the GAPDH target (see Supporting Information Table 3). This value falls within the range found in 72 tissues (from 700 copies/ng RNA of breast tissue to 10 000 copies/ng RNA of muscle tissue) , but it is lower than those extrapolated from other papers . However, even if the absolute number (of copies) found here could be inaccurate, this is of scarce practical consequence for the aim of the present study (see below).…”
Section: Resultssupporting
confidence: 58%
“…The employment of this method allowed us to calculate that 1 ng of the “pooled sample” contained approximatively 5822 copies of the GAPDH target (see Supporting Information Table 3). This value falls within the range found in 72 tissues (from 700 copies/ng RNA of breast tissue to 10 000 copies/ng RNA of muscle tissue) , but it is lower than those extrapolated from other papers . However, even if the absolute number (of copies) found here could be inaccurate, this is of scarce practical consequence for the aim of the present study (see below).…”
Section: Resultssupporting
confidence: 58%
“…Yet, with stability of its expression being suboptimal, it could affect the statistical outcome. Of note, preservation of GAPDH expression upon altered conditions has been reported for human umbical vein endothelial cells (HUVECs) grown under hyperglycemic conditions (Bakhashab et al 2014), chondrocytes cultured at different temperatures (Ito et al 2014) or blood cells subjected to radiation (Vaiphei et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The literature shows different conclusions in relation to the housekeeping genes, for example, Vaiphei ST et al, concluded that, in blood, GAPDH, either alone or in combination with 18S, was found to be the most suitable endogenous control gene (Vaiphei et al, 2014). On the contrary, Moreno LI et al, published that beta-2 microglobulin exhibited the highest expression for all body fluids in forensic applications (Moreno et al, 2012).…”
Section: Resultsmentioning
confidence: 99%